Association of Staphylococcus aureus genotypes with milk or colonization of extramammary sites in Dutch dairy cattle indicates strain variation in reservoirs for intramammary infections. (January 2023) - Exel, Catharina E.; Gerritsen, Kim; Spaninks, Mirlin; Duim, Birgitta; Koop, Gerrit; Benedictus, Lindert
Abstract: Staphylococcus aureus ( S. aureus ) is a major mastitis pathogen with a detrimental impact on udder health in dairy cattle. Although S. aureus is generally classified as a contagious mastitis pathogen, control measures aimed at preventing contagious transmission are not always effective. Previous studies showed that various extramammary sites can be colonized with S. aureus and could be a reservoir for S. aureus intramammary infections (IMI). The aim of this study was to determine the prevalence of S. aureus extramammary site colonization in Dutch dairy cattle and to compare the spa genotypes of S. aureus isolates from IMI to spa genotypes of isolates from extramammary sites. Six herds were visited and from cows with a composite milk somatic cell count ≥200, 000 cells/mL quarter milk samples and swabs from various extramammary sites (hock, groin, udder cleft, nares, and feces) were taken. Extramammary site samples were processed by a two-step high salt selective culture and presence of S. aureus was confirmed by femA PCR. S. aureus isolates from milk and extramammary sites were compared by spa typing. The cow level colonization varied from 0% to 73%, and the prevalence of IMI in the sampled cows varied from 0% to 61% between herds. The extramammary site with the highest prevalence of colonization was the hock (23%) and the lowest prevalence of colonization was found for the nares (5%) and feces (5%). Spa typing of S. aureus isolates from either extramammary sites or milk showed that in most herds there were one or two predominant S. aureus spa genotypes present. Different S. aureus spa genotypes could be categorized into three groups based on the distribution between milk or extramammary sites: i) predominantly milk associated, ii) associated with both milk and extramammary sites, and iii) associated with extramammary sites. In conclusion, we showed that the prevalence of extramammary site colonization differed significantly between herds and extramammary sites and that specific S. aureus spa genotypes were associated with milk (IMI) or extramammary site colonization. Extramammary S. aureus reservoirs could be a source for IMI that cannot be eradicated by intervention measures aimed at contagious mastitis pathogens. Highlights: Cow level S. aureus colonization prevalence varied from 0 to 73% between herds. Intramammary infection prevalence varied from 0% to 61% between herds. Specific S. aureus strains were associated with either milk or extramammary sites. Other S. aureus strains were found equally in both milk and extramammary sites. Extramammary S. aureus reservoirs could be a source for spill-over intramammary infections.